A Supervised Learning Framework in the Context of Multiple Annotators (2023)
The increasing popularity of crowdsourcing platforms, i.e., Amazon Mechanical Turk, is changing how datasets for supervised learning are built. In these cases, instead of having datasets labeled by one source (which is supposed to be an expert who provided the absolute gold standard), we have datasets labeled by multiple annotators with different and unknown expertise. Hence, we face a multi-labeler scenario, which typical supervised learning models cannot tackle.For this reason, much attention has recently been given to the approaches that capture multiple annotators’ wisdom. However, such methods reside on two key assumptions: the labeler’s performance does not depend on the input space and independence among the annotators, which are hardly feasible in real-world settings. This book exploresseveral models based on both frequentist and Bayesian perspectives aiming to face multi-labeler scenarios. Our approaches model the annotators’ behavior by considering the relationship between the input space and the labelers’ performance and coding interdependencies among them.